The Implementation of State Law and Religious Law In Indonesian Muslim Society - Nurhayati, Nurhayati (Jurnal Studi Al-Qur'an, 2017)
In the Indonesian constitution, rule of law is an acknowledged instrument to realize justice and social welfare. Common in many post-colonial countries, this instrument often manifests as legal pluralism, that is the co-existence of at least three legal systems: state (or ‘national’ in Indonesian parlance); religious, and customary (adat in Indonesian language). This paper examined the first two systems, state and religious laws, especially in their implementation as practiced by the Indonesian society. Using empirical legal methods, the factors which influenced the preference of Muslims to use state or religious laws in Indonesia were examined. Key terminologies, such as ‘state law’, ‘religious law’, and ‘Muslim society’, were elaborated. It was found that several factors were influential, namely legal culture, economic condition, social values, fiqh conservatism, and judge insight. Keywords: State Law, Religious Law , Muslim Society